2015
DOI: 10.1371/journal.pone.0137316
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Intra-Retinal Layer Thickness Estimates

Abstract: PurposeMeasurement of intra-retinal layer thickness using optical coherence tomography (OCT) has become increasingly prominent in multiple sclerosis (MS) research. Nevertheless, the approaches used for determining the mean layer thicknesses vary greatly. Insufficient data exist on the reliability of different thickness estimates, which is crucial for their application in clinical studies. This study addresses this lack by evaluating the repeatability of different thickness estimates.MethodsStudies that used in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 47 publications
(55 reference statements)
5
67
0
6
Order By: Relevance
“…We reported the details of segmentation repeatability in annuli and sectors using two partition methods and found that they were comparable. In addition, the repeatabilities in annuli and section were comparable to those reported in previous studies 24,26,40,41. Oberwahrenbrock et al reviewed the reliability of intraretinal thickness measurements and estimated the ICCs and CoRs from previously published data 40.…”
Section: Discussionsupporting
confidence: 78%
“…We reported the details of segmentation repeatability in annuli and sectors using two partition methods and found that they were comparable. In addition, the repeatabilities in annuli and section were comparable to those reported in previous studies 24,26,40,41. Oberwahrenbrock et al reviewed the reliability of intraretinal thickness measurements and estimated the ICCs and CoRs from previously published data 40.…”
Section: Discussionsupporting
confidence: 78%
“…Automatic segmentation results were carefully checked for errors and corrected if necessary by an experienced rater masked for the diagnosis of the subjects. Combined ganglion cell and inner plexiform layer volume (GCIP), inner nuclear layer volume, and outer retinal layers volume including the outer plexiform and nuclear layer, inner and outer photoreceptor segments, and retinal pigment epithelium, were extracted from a 6-mm-diameter cylinder around the fovea [32]. Furthermore, all scans were examined for macular microcysts [19] and other retinal pathologies.…”
Section: Methodsmentioning
confidence: 99%
“…The combined ganglion cell and inner plexiform layer volume (GCIP), inner nuclear layer volume (INL) and total macular volume (TMV) was calculated as a 3 mm diameter cylinder around the fovea from a macular volume scan ( Berlin : 25°×30°, 61 vertical B-scans, 11≤ART≤18; Munich : 20°×20°, 25 vertical B-scans, 21≤ART≤49; Oxford : 69% 30°×25° 61 vertical B-scans, 27% 30°×15° 37 horizontal B-scans, 2% 30°×25° 61 horizontal B-scans, 2% 30°×15° 19 horizontal B-scans, 7≤ART≤22) 20. The fovea thickness (FT) was defined as mean thickness of the 1 mm diameter cylinder around the fovea from the same scan 16.…”
Section: Methodsmentioning
confidence: 99%